2019
DOI: 10.5535/arm.2019.43.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intra-articular Injections of Hyaluronic Acid Combined With Polydeoxyribonucleotide in the Treatment of Knee Osteoarthritis

Abstract: Objective To assess the clinical efficacy and safety of intra-articular injection of hyaluronic acid (HA) combined with polydeoxyribonucleotide (PDRN) in patients with knee osteoarthritis in comparison with that of HA alone. Methods The current single-center, prospective, randomized, double-blind, controlled study was conducted in 36 patients with knee osteoarthritis at our medical institution. All the eligible patients (n=30) were equally assigned to two treatment arms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Kinnaird et al [ 23 ] found that the growth of endothelial cells and smooth muscle cells may be promoted by the use of medium conditioned with MSCs. This phenomenon might be partly explained by the presence of VEGF (vascular endothelial growth factor) and bFGF (basic fibroblast growth factor), which appeared in high levels in a MSC-conditioned medium [ 24 ]. They can recruit macrophages and endothelial cells into the injured site, allowing enhancement of the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Kinnaird et al [ 23 ] found that the growth of endothelial cells and smooth muscle cells may be promoted by the use of medium conditioned with MSCs. This phenomenon might be partly explained by the presence of VEGF (vascular endothelial growth factor) and bFGF (basic fibroblast growth factor), which appeared in high levels in a MSC-conditioned medium [ 24 ]. They can recruit macrophages and endothelial cells into the injured site, allowing enhancement of the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…The adenosine A 2A receptor agonist, polydeoxyribonucleotide (PDRN), exhibits an anti-inflammatory effect by inhibiting pro-inflammatory cytokine production. PDRN is also known to inhibit apoptosis in several disease states such as gastric ulcers, acute lung injury, and osteoarthritis [ 16 18 ]. Despite the excellent pharmacological effects of PDRN, few studies have evaluated the efficacy of PDRN in cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 study confirmed the preventive effect of Ok-PDRN on post-surgery scar formation [ 58 ]. Forty-four patients who underwent open total thyroidectomy were subjected to a combined therapy consisting of fractional laser treatment (48 J/16 cm 2 ) and Ok-PDRN injections during the first four weeks after surgery, after which Ok-PDRN injections were administered for an additional 2-week period.…”
Section: Resultsmentioning
confidence: 99%